MOBILE WEB APPLICATION PURWOKERTO TRADITIONAL FOOD GAME CLASIFICATION USING MOBILENET V2 (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
Indonesia is a large country where there are thousands of aspects of culture, language and tourism. All of these aspects are an identity for the Indonesian state and each region within it. Culinary is one aspect that is included in the field of tourism. In Indonesia, each region has a special food that is an icon of the area. With so many foods from foreign countries entering Indonesia, this is feared will make the younger generation lose their identity about the regional heritage in special foods. Current technological developments have become excellent in various fields to solve the challenges that exist in the surrounding environment, it does not rule out the possibility that technology can be used to preserve the special foods that exist in each region. Based on the problems outlined above, this research will build a mobile web-based application for the introduction of local specialties through imagery and implement computer vision to mobile devices with CNN MobileNet V2 architecture. In this study a mobile web application was produced that was able to recognize Purwokerto's special foods that could be run well on various devices and operating systems.
Keywords: web mobile; computer vision; traditional food